Effects of Montelukast on Arsenic-Induced Epithelial-Mesenchymal Transition and the Role of Reactive Oxygen Species Production in Human Bronchial Epithelial Cells - Chen, Huang-Chi; Chiou, Hsin-Ying Clair; Tsai, Mei-Lan; Chen, Szu-Chia; Lin, Ming-Hong; Chuang, Tzu-Chun; Hung, Chih-Hsing; Kuo, Chao-Hung (Frontiers in Pharmacology, 2022)
Background: Epithelial-mesenchymal transition (EMT) of airway lung epithelial cells is considered a major driver of fibrosis and airway remodeling. Arsenic exposure is well known to cause the malignant transformation of cells, including those in the lung. Accumulating studies have shown that arsenic exposure is associated with chronic pulmonary diseases. However, clinical treatment for arsenic-induced pulmonary damage has not been well investigated. Materials and Methods: The therapeutic effects of montelukast and its combination with fluticasone on sodium arsenite-induced EMT changes in normal human bronchial cells were investigated. The cell migration ability was evaluated by Transwell and wound healing assays. EMT marker expression was determined by immunoblotting. Furthermore, the role of reactive oxygen species (ROS) generation in arsenic-induced EMT and the effect of montelukast on this process were determined by ROS inhibitor treatment and total ROS measurement, respectively. Results: Montelukast was effective at reducing arsenic-induced cell migration and mesenchymal protein (fibronectin, MMP-2, N-cadherin, -catenin, and SMAD2/3) expression. Arsenic-induced total ROS production was attenuated by pretreatment with montelukast. Treatment with the ROS inhibitor N-acetyl cysteine reduced arsenic-induced NF-kB phosphorylation and the mesenchymal protein expression, indicating that total ROS production is critical for arsenic-induced EMT. In addition, combined treatment with montelukast and fluticasone reversed the inhibitory effects of montelukast on cell migration. The expression of fibronectin, MMP-2 induced by arsenic was further enhanced by the combination treatment compared with montelukast treatment only. Conclusion: This study demonstrated that montelukast is effective at reducing arsenic-induced EMT in human bronchial epithelial cells. Through the inhibition of arsenic-induced total ROS generation and NF-kB activation, which is critical for arsenic-induced EMT, montelukast inhibited arsenic-induced cell migration and the expression of extracellular matrix proteins and several EMT-regulating transcription factors. The combination of fluticasone with montelukast reversed the inhibitory effect of montelukast on arsenic-induced EMT. This study provides therapeutic strategies and mechanisms for arsenic-induced pulmonary epithelial damage.